2015
DOI: 10.4322/rca.1731
|View full text |Cite
|
Sign up to set email alerts
|

Produção de mudas de mamoeiro Formosa com diferentes doses de esterco ovino

Abstract: Carica papaya L. Carica papaya L. Carica papaya Estercos Propagação Substratos KEYWORDS Carica papaya L. Carica papaya L. Carica papaya Manure Propagation Substrates RESUMO: O uso de adubos orgânicos resulta em melhorias nas propriedades físicas, químicas e biológicas do substrato, o qual é imprescindível na produção de mudas. Em função do exposto, este trabalho objetivou, com este experimento, avaliar o efeito da aplicação de diferentes doses de esterco ovino sobre a produção de mudas de mamoeiro 'Formosa'. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
2
2
8
Order By: Relevance
“…Similarly, the treatments T1 to T6 led to RDM values that were 113 to 260% higher than that of the control (Table 6). The results obtained by any of the alternative treatments were higher than the maximum found by Costa Júnior et al (2017) at 65 DAS (1.2 g), Oliveira et al (2015) at 40 DAS (0.4 g) and Almeida et al (2018b) at 60 DAS (0.26 g), in Formosa papaya seedlings.…”
Section: Production Of Papaya Seedlingscontrasting
confidence: 64%
See 2 more Smart Citations
“…Similarly, the treatments T1 to T6 led to RDM values that were 113 to 260% higher than that of the control (Table 6). The results obtained by any of the alternative treatments were higher than the maximum found by Costa Júnior et al (2017) at 65 DAS (1.2 g), Oliveira et al (2015) at 40 DAS (0.4 g) and Almeida et al (2018b) at 60 DAS (0.26 g), in Formosa papaya seedlings.…”
Section: Production Of Papaya Seedlingscontrasting
confidence: 64%
“…The results obtained in this study were relatively lower than those obtained by Silva et al (2018b), in the Midwest region, who evaluated the formation of papaya seedlings in different organic substrates and found a maximum number of leaves of 7.8 leaves, at 90 DAS. Similarly, the results were also lower than those obtained in the Northeast region by Costa Júnior et al (2017), who found values between 6 and 9 units at 65 DAS, and those obtained also in the Northeast region by Oliveira et al (2015), who observed values between 5 and 11 units, approximately, at 40 DAS. This may be related to the climatic conditions of the regions where the above-mentioned studies were carried out because, as these regions have higher average temperature, the quality and intensity of light influence the development of the plant.…”
Section: Production Of Papaya Seedlingscontrasting
confidence: 55%
See 1 more Smart Citation
“…A dose de 40% de esterco ovino promoveu o maior NFP, estimado em 25,2 (figura 1), estando esse resultado relacionado à maior disponibilidade de nutrientes nesses substratos. Tais resultados são semelhantes aos encontrados por Oliveira et al (2015), que constataram incremento de 107,7% no NFP de mudas de mamoeiro formosa com a utilização de 60% de esterco ovino na composição do substrato.…”
Section: Resultsunclassified
“…Esta resultância certamente é devido a melhor estruturação do solo, causada pela matéria orgânica e a influencia do nitrogênio, que desempenha uma função vital a planta, visto que o esse nutriente o algodoeiro retira do solo em maior proporção (SILVA et al, 2008). Outrossim, a incorporação de estercos em solos aumenta os teores de matéria orgânica, proporcionando maior capacidade de armazenamento e disponibilidade de água as plantas, bem como a aeração do solo e o desenvolvimento das raízes (OLIVEIRA et al, 2015), melhorando, dessa forma, a estruturação do solo salino-sódio, que por sua vez são desestruturados e impermeáveis (SILVA et al, 2014).…”
Section: Resultsunclassified